1997
DOI: 10.1093/humrep/12.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Absence of glucose decreases human fertilization and sperm movement characteristics in vitro

Abstract: The effect of glucose in a modified Ham's F10 medium (MM) without hypoxanthine, phosphate and transition metals on human fertilization and sperm survival in vitro was determined. Mature human oocytes from in-vitro fertilization (IVF) patients or Percoll-washed human spermatozoa were randomly allocated to one of the treatment groups: normal Ham's F10, MM, MM with 5 mM glucose (HGMM) and MM with 0.5 mM glucose (LGMM). Oocytes were inseminated in one of the four media for 12-20 h and checked for fertilization. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 20 publications
1
39
0
Order By: Relevance
“…To become functionally competent, spermatozoa must undergo capacitation within the female tract (Ecroyd et al 2003) and even though glucose has been reported to be beneficial for human sperm capacitation (Mahadevan et al 1997, Williams & Ford 2001, the present results suggest that high glucose levels do not interfere with this process. To our knowledge the present report is the first to address the effects of high glucose levels on capacitation.…”
Section: Effects Of Glucose On Spermatozoa Functionalitymentioning
confidence: 55%
See 2 more Smart Citations
“…To become functionally competent, spermatozoa must undergo capacitation within the female tract (Ecroyd et al 2003) and even though glucose has been reported to be beneficial for human sperm capacitation (Mahadevan et al 1997, Williams & Ford 2001, the present results suggest that high glucose levels do not interfere with this process. To our knowledge the present report is the first to address the effects of high glucose levels on capacitation.…”
Section: Effects Of Glucose On Spermatozoa Functionalitymentioning
confidence: 55%
“…In accordance, a number of studies have already demonstrated that the capacitation of human spermatozoa substantially relies on glucose, which suggests a key role for glucose in sustaining hyperactivation (Williams & Ford 2001), in tyrosine phosphorylation (Travis et al 2001), and in ensuring IVF (Rogers & Perreault 1990, Mahadevan et al 1997. However, it is still unclear whether the beneficial effects of glucose derive from the provision of extra metabolic energy through glycolysis or from the generation of other metabolic products (Aitken et al 1997, De Lamirande et al 1997, Williams & Ford 2001.…”
Section: Effects Of Substrate Availability On Spermatozoa Functionalitymentioning
confidence: 96%
See 1 more Smart Citation
“…Nevertheless, anaerobic glycolysis seems to be the most important source of energy to human sperm, and is important to sperm motility [67,68], capacitation [69], and fertilization ability [67]. Triacylglycerols are a source of fatty acids, which are also important for sperm metabolism [70,71].…”
Section: Conserved Functionsmentioning
confidence: 99%
“…These differences are of profound importance when handling gametes in vitro. For example, glucose will inhibit capacitation in bull sperm, but is required for capacitation in mouse sperm.The role of glucose in sperm metabolism of other species remains under investigation (Quinn et al 1995;Mahadevan et al 1997;Barak et al 1998;Williams and Ford 2001).…”
Section: Fuel Support and More: The Fibrous Sheathmentioning
confidence: 99%